Economic outlook for representative cotton farms given the August 2012 FAPRI/AFPC Baseline - James W. Richardson; Joe L. Outlaw; George M. Knapek; J. Marc Raulston (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2012)
The Agricultural and Food Policy Center (AFPC) at Texas A&M University develops and maintains data to simulate sixteen representative cotton operations in major production areas of eight states. The chief purpose of this analysis is to project the economic viability of those farms from 2012 through 2017. The data necessary to simulate the economic activity of these operations is developed through ongoing cooperation with panels of agricultural producers in each of these states. The Food and Agricultural Policy Research Institute (FAPRI) provided projected prices, policy variables, and input inflation rates in their August 2012 Baseline. This analysis assumes continuation of 2008 farm bill provisions throughout the study period. Under the August 2012 Baseline, eleven of the representative cotton farms are in good liquidity condition (less than a 25 percent chance of negative ending cash in 2017). One farm (TXSP2500) has a 25 percent to 50 percent likelihood of negative ending cash. The remaining four farms (TXRP2500, TXMC1800, TXCB2500, and ARNC5000) have a greater than 50 percent chance of negative ending cash. Farms are also classified based on their respective equity conditions. Eight farms are classified in good equity position (less than a 25 percent chance of decreasing real net worth during 2012-2017). Seven representative cotton farms have between a 25 percent and 50 percent likelihood of losing real net worth, and one farm (TXRP2500) has a greater than 50 percent probability of decreasing real net worth. Overall rankings based on combined liquidity and equity rankings for the representative cotton farms are projected to be as follows: Eight of the sixteen farms are classified in good condition, four are in marginal condition, and four are in poor condition. Lower cotton prices under the most recent projections in the August 2012 Baseline have resulted in an slight decline in the overall financial outlook for cotton farms, as the current baseline results in one less farm classified as good and one more farm classified as poor as compared to the January 2012 Baseline. Current price projections for cotton throughout the study period are all slightly below the target price of 0.7125/lb as specified in the 2008 farm bill. Lower projected prices for cotton coupled with increases in rates of change for input prices, especially in the near-term, have resulted in a slightly less optimistic outlook for AFPC representative cotton farms under the current baseline.
Keywords: 330